Urban Agriculture, Commons and Urban Policies: Scaling up Local Innovation - François Mancebo (Challenges in Sustainability, 2016)
May urban agriculture be the cornerstone that helps reconfigure more sustainable cities and if so, under which conditions? And if so, what type of urban agriculture? Such are the two issues underlying this article. Why not counteracting urban sprawl by fostering what could be called “rural sprawl”, by introducing nature and rural characteristics such as farming within the city, in its interstitial areas and wastelands? In this perspective, urban agriculture becomes a common good, bringing people together and reshaping the whole urban fabric that would eventually propose a radical remaking of the urban. Urban agriculture lends particularly well to long-lasting urban policies, especially those turning environmental “bads”—such as brownfields and wastelands—into environmental “goods” and urban amenities. Urban agriculture in interstitial abandoned urban areas may be one of cities’ main seedbeds of creative innovation. It is all about the right to decide and the power to create, renewing and deepening what Henri Lefebvre called The Right to the City.